Research and Improvement on the Algorithm of Heuristic P-cycle Construction - NI Jun-hong; LIU Xin-tong (Guangtongxin yanjiu, 2016)
To solve the defects of P-cycle generating algorithm named Grow,a NewGrow algorithm is proposed in this paper.It first calculates all optional cycles’ AE,and then expands the selecting candidate P-cycles.The simulation is conducted in the network topology.The simulation results show that the new method can improve the quality of P-cycles,and reduce the number of P-cycles,as well as the burden of network nodes and improve the network resource utilization.